Legal Studies and Muslim Scholars Opinion on the Indonesia's National Health Insurances | فتوى مجلس العلماء الإندونيسي عن التأمين الاجتماعي (BPJS) في إندونيسيا - Husni Mubarak A. Latif (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
The article would like to discuss on fatwa (Islamic legal opinion) of Social Insurance (BPJS) issued by The Council of Indonesian Ulama (MUI) in 2015. By using the contents of fatwa as the main data source to be analyzed, this article would like to dig in depth and elaborate more what are the reasons as well as legal reasoning that drove MUI in issuing such fatwa? What aspects of BPJS practices those are not in accordance with Islamic sharia law? This fatwa, however, is in line with previous fatwa which has been issued by MUI in year 2001 on Guideline for Islamic Insurance. This article finds that in MUI’s view, the operational system of BPJS still shackled within the framework of conventional insurance so that should be converted into sharia insurance framework to avoid speculative, uncertainty and usury which are the most forbidden things within Islamic sharia.